Amyloid β‐abrogated TrkA ubiquitination in PC12 cells analogous to Alzheimer's disease. (19th March 2015) - Zheng, Chen; Geetha, Thangiah; Gearing, Marla; Ramesh Babu, Jeganathan
Abstract Amyloid beta (Aβ) protein is the primary proteinaceous deposit found in the brains of patients with Alzheimer's disease (AD). Evidence suggests that Aβ plays a central role in the development of AD pathology. Here, we show in PC12 cells, Aβ impairs tropomyosin receptor kinase A (TrkA) ubiquitination, phosphorylation, and its association with p75NTR, p62, and TRAF6 induced by nerve growth factor. The ubiquitination and tyrosine phosphorylation of TrkA was also found to be impaired in postmortem human AD hippocampus compared to control. Interestingly, the nitrotyrosylation of TrkA was increased in AD hippocampus and this explains why the phosphotyrosylation and ubiquitination of TrkA was impaired. In AD brain, the production of matrix metalloproteinase‐7 (MMP‐7), which cleaves proNGF, was reduced, thereby leading to the accumulation of pro‐NGF and a decrease in the level of active NGF. TrkA signaling events, including Ras/MAPK and phosphatidylinositol 3‐kinase (PI3K)/Akt pathways, are deactivated with Aβ and in the human AD hippocampus. Findings show that Aβ blocks the TrkA ubiquitination and downstream signaling similar to AD hippocampus. Cell survival and differentiation are essential for living organisms. We propose that under normal conditions, nerve growth factor (NGF) leads to Tropomyosin receptor kinase A (TrkA) phosphorylation, ubiquitination and its association with p75NTR, p62 and TRAF6, thereby promoting cell survival and differentiation. In diseased conditions such as Alzheimer's, proNGF leads to nitrotyrosylation of TrkA, thereby impairing its ubiquitination and downstream signaling which results in apoptosis. TRAF6 = tumor necrosis factor receptor‐associated factor 6; Ub = ubiquitin.